Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1159/000006876
|View full text |Cite
|
Sign up to set email alerts
|

Soluble PECAM-1, but Not P-Selectin, Nor Osteonectin Identify Acute Myocardial Infarction in Patients Presenting with Chest Pain

Abstract: We sought to determine plasma levels of platelet/endothelial cell adhesion molecule-1 (PECAM-1), P-selectin, and platelet-derived osteonectin, and prospectively compare these data with the discharge diagnosis in patients presenting with chest pain in a community hospital Emergency Department. Soluble antigens were measured by ELISA in 44 subjects including patients with acute myocardial infarction (AMI) (n = 13), chest pain of noncardiac origin (n = 17), and compared to those of age- and sex-matched healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
6
18
0
Order By: Relevance
“…The increase in the sPECAM-1 levels at acute event of MI is in consistent with its role in atherosclerosis and thrombosis. Similar finding has been reported by Serebruany et al [21] and Soeki et al [22]. The decreased levels of sPECAM-1 observed in treated MI patients in the present study may be accounted by the intense medical treatment received by these patients and that their blood sample was collected on an average 4.5 days from the stabilization of their symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in the sPECAM-1 levels at acute event of MI is in consistent with its role in atherosclerosis and thrombosis. Similar finding has been reported by Serebruany et al [21] and Soeki et al [22]. The decreased levels of sPECAM-1 observed in treated MI patients in the present study may be accounted by the intense medical treatment received by these patients and that their blood sample was collected on an average 4.5 days from the stabilization of their symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been demonstrated to have role in plaque formation and thrombosis (Newman et al, 1990, Mahooti et al, 2000. In our study there was significant increase in sPECAM-1 in AMI patients at acute event consistent with the finding of Serebruany et al (1999b) and Soeki et al (2003).…”
Section: Platelet Endothelial Cell Adhesion Molecule (Pecam-1)supporting
confidence: 90%
“…In both platelets and endothelial cells, PECAM‐1 is shed into the plasma after proteolytic cleavage of its ectodomain. sPECAM‐1 is consistently and significantly increased in humans with acute myocardial infarction, as well as in patients with congestive heart failure independent of disease origin 35, 36. Similar results have been documented by Soeki et al, who suggested that increased sPECAM‐1 concentrations may be a sensitive marker for the early diagnosis of acute cardiac disease in humans 35.…”
Section: Discussionmentioning
confidence: 55%